1994
DOI: 10.1108/08876049410065624
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Servicescapes in Leisure Service Settings

Abstract: Services marketing research has largely focussed on measuring service quality and satisfaction associated with the primary service itself, with little attention given to the effect of the physical surroundings of the service setting. Leisure services in particular, may be concerned with how consumers perceive the quality of the “servicescape” and what effect the servicescape has on customer satisfaction and repatronage. Investigates these effects, as well as the interactions of perceived crowding, excitement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
329
3
39

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 503 publications
(403 citation statements)
references
References 12 publications
13
329
3
39
Order By: Relevance
“…Bolton & Lemon, 1999;Nguyen & Leblanc, 2002;Reimer & Kuehn, 2005;Ryu & Jang, 2007;Varki & Colgate, 2001). The importance of the physical environment in influencing behaviour s has been verified in many consumer behaviour studies such as by Reimer and Kuehn (2005), and Wakefield and Blodgett (1994). It was found that making the atmosphere more pleasant and innovative was essential for a firm's success.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Bolton & Lemon, 1999;Nguyen & Leblanc, 2002;Reimer & Kuehn, 2005;Ryu & Jang, 2007;Varki & Colgate, 2001). The importance of the physical environment in influencing behaviour s has been verified in many consumer behaviour studies such as by Reimer and Kuehn (2005), and Wakefield and Blodgett (1994). It was found that making the atmosphere more pleasant and innovative was essential for a firm's success.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Customers tend to evaluate the attractiveness of the place when they approach it, even outside of it. Once inside, customers of leisure services spend hours examining (consciously and unconsciously) the venue (Wakefield & Blodgett, 1994).…”
Section: Research Framework and Methodologymentioning
confidence: 99%
“…Since customers evaluate the entire service encounter, not just the initial interaction with the provider (Brown & Swartz, 1989), a failure in one aspect of that encounter may influence the extent that customers use criteria other than the service success in evaluating satisfaction with the overall service performance (Taylor & Claxton, 1994). Thus, many aspects of the service encounter may affect a customer's level of satisfaction to a greater degree than just service success (Wakefield & Blodgett, 1994;Mohr & Bitner, 1995). While the specific salient criteria may vary, customers judge the ability of a service provider to comply with their subjective expectations relative to these criteria.…”
mentioning
confidence: 99%